Validating the Blockchain Benchmarking Framework Through Controlled Deployments of XRPL and Ethereum - Marios Touloupou; Klitos Christodoulou; Marinos Themistocleous (IEEE Access, 2024)
In the evolving domain of blockchain, a critical challenge lies in the performance analysis of blockchains under controlled test conditions. This paper focuses on validating the Blockchain Benchmarking Framework (BBF), developed for the evaluation of blockchain protocols in a controlled environment. The BBF’s robustness and versatility are demonstrated through its application to the official Docker clients of Ripple’s XRP Ledger (XRPL) and Ethereum, deployed in private, local and controlled environments. These deployments are utilized to simulate network dynamics, transaction throughput, and resilience in a variety of scenarios. Our methodology encompasses tests ranging from standard operational conditions to adverse scenarios, including node failures and simulated double-spend attacks. These controlled environments are essential for evaluating the BBF’s efficacy in stress testing blockchain protocols and assessing their stability and robustness. The BBF’s ability to accurately capture and analyze performance characteristics is highlighted, providing insights into the operational mechanics, scalability, and resilience of these blockchain clients. The findings emphasize the BBF’s adaptability and effectiveness in managing different blockchain protocols, reaffirming its potential for broader application in pre-launch testing and analysis of blockchain performance. This study contributes to the understanding of how blockchain clients can be preliminarily assessed before mainnet deployment as well as to validate all the design decisions made by the protocol under different settings and synthetic scenarios.